Correlations Between the Thermosphere's Semiannual Density Variations and Infrared Emissions Measured With the SABER Instrument. Issue 10 (27th October 2018) - Weimer, D. R.; Mlynczak, M. G.; Emmert, J. T.; Doornbos, E.; Sutton, E. K.; Hunt, L. A.
Abstract: This paper presents measurements of the amplitudes and timings of the combined, annual, and semiannual variations of thermospheric neutral density, and a comparison of these density variations with measurements of the infrared emissions from carbon dioxide and nitric oxide in the thermosphere. The density values were obtained from measurements of the atmospheric drag experienced by the Challenging Minisatellite Payload, Gravity Recovery and Climate Experiment A, Gravity field and Ocean Circulation Explorer, and three Swarm satellites, while the optical emissions were measured with the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) instrument on the Thermosphere Ionosphere Mesosphere Energetics and Dynamics satellite. These data span a time period of 16 years. A database containing global average densities that were derived from the orbits of about 5, 000 objects (Emmert, 2009, https://doi.org/10.1029/2009JA014102, 2015b, https://doi.org/10.1002/2015JA021047 ) was employed for calibrating these density data. A comparison with the NRLMSISE‐00 model was used to derive measurements of how much the density changes over time due to these seasonal variations. It is found that the seasonal density oscillations have significant variations in amplitude and timing. In order to test the practicality of using optical emissions as a monitoring tool, the SABER data were fit to the measured variations. Even the most simple fit that used only filtered carbon dioxide emissions had good correlations with the measured oscillations. However, the density oscillations were also well predicted by a simple Fourier series, contrary to original expectations. Nevertheless, measurements of the optical emissions from the thermosphere are expected to have a role in future understanding and prediction of the semiannual variations. Plain Language Summary: The uppermost atmosphere, known as the thermosphere, undergoes oscillations in the density of the neutral atoms and molecules, producing two peaks and valleys in the density in each year. The timing of of these "semiannual" variations or oscillations, as well as their amplitudes, tends to vary. Their unpredictability makes it harder to accurately model the amount of drag experienced by orbiting satellites. It had been noticed that the infrared light emitted by carbon dioxide molecules in the thermosphere has a tendency to follow the semiannual oscillations. Such emissions have been measured by an instrument on a NASA satellite for the past 16 years. We have compared these emissions with the variations in the semiannual oscillations that were derived from measurements of the drag seen by six different satellites flown by both NASA and the European Space Agency during the same time period, though not at the same time. The results of the comparison show how well the infrared emissions match the density oscillations, due to changes in both the composition and temperature of the thermosphere that influence both. Results show that further study will be needed to be able to accurately predict the density oscillations. Key Points: Four satellite missions are used to derive thermosphere density variations caused by annual and semiannual oscillations over a 16‐year period Variations in thermospheric density are compared with emissions from carbon dioxide and nitric oxide measured with the SABER instrument The carbon dioxide emissions and simple Fourier series fits have good correlations with thermosphere density oscillations